A lithium ion battery positive electrode material and preparation method thereof, and a lithium ion battery

By coating F-doped iron cobaltate on the lithium-rich manganese-based positive electrode material, the problem of insufficient structural stability and rate performance under high pressure is solved, and higher structural stability and rate capacity are achieved.

CN119447273BActive Publication Date: 2025-04-29GANZHOU NOVA TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510037676.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-29
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

The structural stability of lithium-rich manganese-based positive electrode materials under high pressure is poor, which affects its actual application, and the rate performance is limited, resulting in a low actual rate capacity.

Method used

F-doped iron cobaltate (FeCo2O4-0.5xFx) was used as the cladding layer, and part of the surface of the lithium-rich manganese-based positive electrode material was coated, and the positive electrode material was prepared by coprecipitation reaction and sintering process.

Benefits of technology

It effectively improves the structural stability of lithium-rich manganese-based positive electrode materials, improves its magnification capacity and ion diffusion rate, and improves conductivity and electrochemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447273B_ABST
    Figure CN119447273B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium-ion batteries, and specifically discloses a lithium-ion battery cathode material, a preparation method thereof, and a lithium-ion battery. The lithium-ion battery cathode material includes a lithium-rich manganese-based cathode material and F-doped iron cobaltate coated on at least a part of the surface of the lithium-rich manganese-based cathode material, wherein: the chemical formula of the F-doped iron cobaltate is FeCo2O 4‑0.5x F x , 0.01 ≤ x ≤ 0.06. The lithium-ion battery cathode material of the present invention uses FeCo2O 4‑0.5x F x to coat the lithium-rich manganese-based cathode material, which can effectively improve the structural stability of the lithium-rich manganese-based cathode material, and moreover, the FeCo2O 4‑0.5x F x coating layer has a high Fermi level and excellent electrical conductivity, and can effectively improve the ionic conductivity of the lithium-rich manganese-based material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium ion battery positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium-rich manganese-based positive electrode materials have significant advantages such as high energy density, long cycle life, environmental friendliness, low cost and good stability. They are expected to match high specific capacity / high voltage positive electrodes and metal lithium negative electrodes for stable operation. Therefore, compared with the currently commercialized positive electrode materials, lithium-rich manganese-based positive electrode materials have huge room for improvement in energy density, safety, stability, etc., and are internationally recognized as positive electrode materials with development potential. However, due to the poor structural stability of lithium-rich manganese-based materials under high pressure, their practical application is seriously affected; in addition, the rate performance of lithium-rich manganese-based materials is limited, so their actual rate capacity is not high. Therefore, how to further improve the structural stability of lithium-rich manganese-based materials and increase their rate capacity is an urgent problem to be solved. Summary of the invention

[0003] The purpose of the present invention is to provide a lithium ion battery positive electrode material with good structural stability and high rate capacity and a preparation method thereof, and a lithium ion battery.

[0004] In the first aspect, the present invention provides a positive electrode material for a lithium-ion battery, which adopts the following technical solution:

[0005] A positive electrode material for a lithium-ion battery, comprising a lithium-rich manganese-based positive electrode material and F-doped iron cobaltate coated on at least a portion of the surface of the lithium-rich manganese-based positive electrode material, wherein the chemical formula of the F-doped iron cobaltate is FeCo 2 O 4-0.5x F x , 0.01≤x≤0.06.

[0006] Preferably, the mass ratio of the F-doped iron cobaltate to the lithium-rich manganese-based positive electrode material is (0.03~0.1):1.

[0007] Preferably, the F-doped iron cobaltate is a nanosheet structure.

[0008] Preferably, the chemical formula of the lithium-rich manganese-based positive electrode material is Li 1+m Mn 1-m-n X n O 2 , wherein: X is one or more of Ni, Co, Fe, Al, and Zn, 0.1≤m≤0.5, 0≤n≤0.4.

[0009] In a second aspect, the present invention provides a method for preparing a positive electrode material for a lithium ion battery, comprising the following steps:

[0010] (1) Dissolve iron salt and cobalt salt in water, then add an organic amine source for coprecipitation reaction to obtain FeCo-LDH;

[0011] (2) adding the FeCo-LDH material prepared in step (1) into a fluoride salt solution and reacting under closed conditions to obtain F-ion-doped FeCo-LDH;

[0012] (3) ball-milling the lithium-rich manganese-based positive electrode material and the F-ion-doped FeCo-LDH prepared in step (2) to obtain a mixture; and sintering the mixture under an inert atmosphere to obtain a lithium-ion battery positive electrode material.

[0013] Preferably, in step (1), the cobalt salt is one or more of cobalt acetate, cobalt sulfate and cobalt nitrate; and the iron salt is one or more of ferrous acetate, ferrous sulfate and ferrous nitrate.

[0014] The organic amine source is one or more of hexamethylenetetramine, azodicarbonamide, triethylenetetramine and tetraethylenepentamine.

[0015] Preferably, in step (1), the iron salt and the cobalt salt are added in a molar ratio of Fe to Co of 1:2.

[0016] Preferably, in step (1), the molar ratio of the cobalt salt to the organic amine source is (0.03-0.1):(1.2-12).

[0017] Preferably, in step (1), after the iron salt and the cobalt salt are dissolved in water, the organic sulfonate or the organic sulfate is added before the organic amine source is added.

[0018] Further preferably, the organic sulfonate or organic sulfate is one or more of sodium dodecyl sulfate, sodium anthraquinone-2-sulfonate monohydrate, and sodium p-toluenesulfonate; and the molar ratio of the cobalt salt to the organic sulfonate or organic sulfate is (0.03-0.1):(1-10).

[0019] Preferably, in step (1), the coprecipitation reaction temperature is 50-80° C.; and the coprecipitation reaction time is 8-15 h.

[0020] Preferably, in step (2), the fluoride salt is one or both of ammonium fluoride and sodium fluoride; and the fluoride salt solution is a fluoride salt aqueous solution.

[0021] Preferably, in step (2), the molar ratio of the F element in the fluoride salt to the Fe element in FeCo-LDH is (0.01-0.06):1.

[0022] Preferably, in step (2), the reaction temperature is 60-90° C., and the reaction time is 10-20 h.

[0023] Preferably, in step (3), the inert atmosphere is an argon atmosphere or a nitrogen atmosphere, the sintering temperature is 500-700° C., and the sintering time is 3-8 hours.

[0024] A third aspect is a lithium-ion battery, wherein the positive electrode material thereof adopts the aforementioned lithium-ion battery positive electrode material.

[0025] The above one or more technical solutions of the present invention can achieve at least one of the following beneficial effects:

[0026] (1) FeCo is used in the present invention 2 O 4-0.5x F x Coating the lithium-rich manganese-based positive electrode material can effectively improve the structural stability of the lithium-rich manganese-based positive electrode material; and FeCo 2 O 4-0.5x F x The coating layer has a high Fermi level and excellent electrical conductivity, and can effectively improve the ionic conductivity of lithium-rich manganese-based materials.

[0027] (2) FeCo 2 O 4-0.5x F x The nanosheet structure can promote the deintercalation of ions. 2 O 4-0.5x F x As a coating layer, it can effectively increase the ion diffusion rate of the positive electrode material and improve the rate performance of the positive electrode material.

[0028] (3) FeCo 2 O 4-0.5x F x F ion doping can optimize the crystal structure of iron cobalt oxide, reduce the diffusion resistance of lithium ions in the electrochemical process, and effectively improve the conductivity of iron cobalt oxide. 2 O 4-0.5x F x As a coating layer, it can improve the lithium ion diffusion efficiency and conductivity of the positive electrode material.

[0029] (4) In the preparation method of the lithium ion positive electrode material of the present invention, organic sulfonate or organic sulfate is added to further adjust the dispersibility of the FeCo-LDH nanosheets, thereby better promoting the deintercalation of lithium ions, thereby better improving the electrochemical performance of the lithium ion battery positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the SEM image of the talc-like F-ion-doped FeCo-LDH prepared in Example 1.

[0031] Figure 2 The cycle performance diagram of the battery assembled with the lithium-ion battery positive electrode materials prepared in Example 1 and Comparative Examples 1-3.

[0032] Figure 3 The cycle performance diagram of the battery assembled with the lithium-ion battery positive electrode materials prepared in Examples 1 to 3 and Examples 6 to 8.

[0033] Figure 4 The cycle performance diagram of the battery assembled with the lithium-ion battery positive electrode materials prepared in Examples 2 and 4-5. DETAILED DESCRIPTION

[0034] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0035] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0036] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0037] Preparation Example 1

[0038] 0.067 molMnSO 4 ·H 2 O and 0.033molCoSO 4 6H 2 O was dissolved in deionized water to prepare a 2 mol / L metal ion solution; then, under the protection of a nitrogen atmosphere, the metal ion solution was added to a continuous stirred tank reactor, and 4 mol / L NaOH precipitant and 20 wt% NH 3 ·H 2 After the complexing agent O was added, the total amount of the precipitant and the complexing agent was 0.15 mol, and the pH of the reaction solution was kept in the range of 10-11. After sufficient reaction for 40 hours, the reaction solution was filtered, and the filter cake was washed with water, alcohol and dried to obtain Mn 0.67 Co 0.33 (OH) 2 .

[0039] 0.1 molMn 0.67 Co 0.33 (OH) 2After mechanically mixing with 0.123 mol of lithium hydroxide, it was placed in a muffle furnace and sintered at 980 ° C for 20 h to finally obtain Li 1.1 Mn 0.6 Co 0.3 O 2 .

[0040] Preparation Example 2

[0041] 0.075 molMnSO 4 ·H 2 O and 0.025molCoSO 4 6H 2 O was dissolved in deionized water to prepare a 2 mol / L metal ion solution; then, under the protection of a nitrogen atmosphere, the metal ion solution was added to a continuous stirred tank reactor, and 4 mol / L NaOH precipitant and 20 wt% NH 3 ·H 2 After the complexing agent O was added, the total amount of the precipitant and the complexing agent was 0.15 mol, and the pH of the reaction solution was kept in the range of 10-11. After sufficient reaction for 40 hours, the reaction solution was filtered, and the filter cake was washed with water, washed with alcohol, and dried to obtain Mn 0.75 Co 0.25 (OH) 2 .

[0042] 0.1 molMn 0.75 Co 0.25 (OH) 2 After mechanically mixing with 0.154 mol of lithium hydroxide, it was placed in a muffle furnace and sintered at 980 ° C for 20 h to finally obtain Li 1.2 Mn 0.6 Co 0.2 O 2 .

[0043] Preparation Example 3

[0044] 0.08 molMnSO 4 ·H 2 O and 0.02molCoSO 4 6H 2 O was dissolved in deionized water to prepare a 2 mol / L metal ion solution; then, under the protection of a nitrogen atmosphere, the metal ion solution was added to a continuous stirred tank reactor, and 4 mol / L NaOH precipitant and 20 wt% NH 3 ·H 2After the complexing agent O was added, the total amount of the precipitant and the complexing agent was 0.15 mol, and the pH of the reaction solution was kept in the range of 10-11. After sufficient reaction for 40 hours, the reaction solution was filtered, and the filter cake was washed with water, washed with alcohol, and dried to obtain Mn 0.8 Co 0.2 (OH) 2 .

[0045] 0.1 molMn 0.8 Co 0.2 (OH) 2 After mechanically mixing with 0.306 mol of lithium hydroxide, it was placed in a muffle furnace and sintered at 980 ° C for 20 h to finally obtain Li 1.5 Mn 0.4 Co 0.1 O 2 .

[0046] Example 1

[0047] This example is a method for preparing Li 1.1 Mn 0.6 Co 0.3 O 2 Coating is carried out, and the coating material is FeCo 2 O 3.99 F 0.02 Nanosheets.

[0048] The specific preparation method is as follows:

[0049] (1) Dissolve 6 mmol of ferrous acetate and 12 mmol of cobalt nitrate in 100 ml of deionized water, then add 0.24 mol of sodium dodecyl sulfate, stir evenly, and then add 0.3 mol of hexamethylenetetramine. Then, coprecipitation reaction is carried out at 70 °C for 10 h to obtain talc-like FeCo-LDH.

[0050] (2) preparing a 0.012 mmol / mL aqueous solution of ammonium fluoride; placing 10 mL of the aqueous solution of ammonium fluoride in a sealed reaction tank, and adding the talc-like FeCo-LDH (6 mmol) prepared in step (1) into the reaction tank, followed by heating and stirring at 80°C for 16 h. After the reaction is completed, filtering is performed, and the filter cake is washed with water, washed with alcohol, and dried to obtain talc-like F-ion-doped FeCo-LDH.

[0051] (3) 5gLi 1.1 Mn 0.6 Co .0.3 O 2The mixture was ball-milled with 0.25 g of talc-like F-doped FeCo-LDH prepared in step (2) to obtain a mixed powder. The mixed powder was placed in a tube furnace and sintered at 630° C. for 4 h in a nitrogen atmosphere to obtain a positive electrode material FeCo 2 O 3.99 F 0.02 @Li 1.1 Mn 0.6 Co 0.3 O 2 .

[0052] Figure 1 This is a SEM image of the talc-like F-ion-doped FeCo-LDH prepared in step (2) of this embodiment. It can be seen from the image that the F-ion-doped FeCo-LDH material is a layered nanosheet structure.

[0053] Comparative Example 1

[0054] Directly adopt Preparation Example 1 to prepare Li 1.1 Mn 0.6 Co 0.3 O 2 As positive electrode material.

[0055] Comparative Example 2

[0056] 5gLi 1.1 Mn 0.6 Co 0.3 O 2 and 0.25 g of commercially available FeCo 2 O 4 The mixed powder was placed in a tube furnace and sintered at 630°C for 4 h in a nitrogen atmosphere to obtain the positive electrode material FeCo 2 O 4 @Li 1.1 Mn 0.6 Co 0.3 O 2 ; Among them: FeCo 2 O 4 It is a nanoparticle structure.

[0057] Comparative Example 3

[0058] The method is basically the same as Example 1, except that: the fluorine ion doping in step (2) is not performed; in step (3), talc-like FeCo-LDH is used to replace the talc-like F ion-doped FeCo-LDH; the positive electrode material prepared is FeCo 2 O 4 @Li 1.1 Mn 0.6 Co 0.3 O2 ; Among them: FeCo 2 O 4 It is a nanosheet structure.

[0059] Example 2

[0060] This example is a method for preparing Li 1.1 Mn 0.6 Co 0.3 O 2 Coating is carried out, and the coating material is FeCo 2 O 3.98 F 0.04 Nanosheets.

[0061] The preparation method is basically the same as that of Example 1, except that in step (2), the concentration of the ammonium fluoride aqueous solution is 0.024 mmol / mL.

[0062] Example 3

[0063] This example is a method for preparing Li 1.1 Mn 0.6 Co 0.3 O 2 Coating modification is carried out, and the coating material is FeCo 2 O 3.97 F 0.06 Nanosheets.

[0064] The preparation method is basically the same as that of Example 1, except that in step (2), the concentration of the ammonium fluoride aqueous solution is 0.036 mmol / mL.

[0065] Example 4

[0066] The method is basically the same as Example 2, except that in step (3), the amount of talc-like F-ion-doped FeCo-LDH added is 0.05 g.

[0067] Example 5

[0068] The method is basically the same as Example 2, except that in step (3), the amount of talc-like F-ion-doped FeCo-LDH added is 0.5 g.

[0069] Example 6

[0070] The method is basically the same as Example 1, except that in step (1), sodium dodecyl sulfate is not added.

[0071] Example 7

[0072] This example is to prepare Li 1.2 Mn 0.6 Co 0.2 O 2Coating modification is carried out, and the coating material is FeCo 2 O 3.985 F 0.03 Nanosheets.

[0073] The specific preparation method is as follows:

[0074] (1) Dissolve 6 mmol of ferrous acetate and 12 mmol of cobalt nitrate in 200 ml of deionized water, then add 0.36 mol of sodium anthraquinone-2-sulfonate monohydrate, stir evenly, and then add 0.48 mol of azodicarbonamide. Then, coprecipitation reaction is carried out at 50 °C for 15 h to obtain talc-like FeCo-LDH.

[0075] (2) preparing a 0.018 mmol / mL aqueous solution of ammonium fluoride; placing 10 mL of the aqueous solution of ammonium fluoride in a sealed reaction tank, and adding the talc-like FeCo-LDH (6 mmol) prepared in step (1) into the reaction tank, followed by heating and stirring at 60° C. for 20 h. After the reaction is completed, filtering is performed, and the filter cake is washed with water, washed with alcohol, and dried to obtain talc-like F-ion-doped FeCo-LDH.

[0076] (3) 5 g Li 1.2 Mn 0.6 Co 0.2 O 2 The mixed powder was ball-milled with 0.20 g of the talc-like F-ion-doped FeCo-LDH prepared in step (2) to obtain a mixed powder; the mixed powder was placed in a tube furnace and sintered at 500° C. for 8 h in a nitrogen atmosphere to obtain a positive electrode material FeCo 2 O 3.985 F 0.03 @Li 1.2 Mn 0.6 Co 0.2 O 2 .

[0077] Example 8

[0078] This example is a method for preparing Li 1.5 Mn 0.4 Co 0.1 O 2 Coating modification is carried out, and the coating material is FeCo 2 O 3.975 F 0.05 Nanosheets.

[0079] The specific preparation method is as follows:

[0080] (1) 6 mmol of ferrous acetate and 12 mmol of cobalt nitrate were dissolved in 80 ml of deionized water, and then 0.12 mol of sodium p-toluenesulfonate was added thereto. After stirring evenly, 0.18 mol of triethylenetetramine was added, and then a coprecipitation reaction was carried out at 80 °C for 8 h to obtain talc-like FeCo-LDH.

[0081] (2) preparing a 0.03 mmol / mL sodium fluoride aqueous solution; placing 10 mL of the sodium fluoride aqueous solution in a sealed reaction tank, and adding the talc-like FeCo-LDH (6 mmol) prepared in step (1) into the reaction tank, followed by heating and stirring at 90° C. for 10 h. After the reaction is completed, filtering is performed, and the filter cake is washed with water, washed with alcohol, and dried to obtain a talc-like F-ion-doped FeCo-LDH material.

[0082] (3) 5gLi 1.5 Mn 0.4 Co 0.1 O 2 The mixed powder was ball-milled with 0.30 g of the talc-like F-ion-doped FeCo-LDH prepared in step (2) to obtain a mixed powder; the mixed powder was placed in a tube furnace and sintered at 700° C. for 3 h in a nitrogen atmosphere to obtain a positive electrode material FeCo 2 O 3.975 F 0.05 @Li 1.5 Mn 0.4 Co 0.1 O 2 .

[0083] The battery assembly is completed by:

[0084] The positive electrode materials prepared in Examples 1 to 8 and Comparative Examples 1 to 3 were assembled into batteries. The positive electrode materials: conductive graphite: PVDF were weighed and ground according to a mass ratio of 8:1:1. Then, an appropriate amount of N-methylpyrrolidone (NMP) was added and continued to be ground and stirred to form a uniform slurry. The slurry was evenly coated on aluminum foil with a mold to a coating thickness of 200 μm. The slurry was placed in a drying oven at 90°C for 10 hours and then cut into discs with a diameter of 12 mm. The disc was used as the positive electrode, the lithium sheet was used as the negative electrode, and the electrolyte included a solvent and LiPF 6 , among which LiPF 6 The concentration is 1mol / L, and the solvent of the electrolyte is a mixed solvent of EC, DEC and DMC with a volume ratio of 1:1:1. The battery is assembled in the glove box in the order of button cell assembly. The performance test of the assembled battery is carried out: the assembled battery that has been left to stand overnight is placed in the LAND2001CT battery test box for charge and discharge test. The test is carried out at 25℃, 1C, and a cycle voltage of 2~4V. The number of cycles is 100. The test results can be seen Figures 2~4and Table 1.

[0085] Table 1

[0086]

[0087] from Figure 2 As can be seen from Table 1, the battery assembled with the positive electrode material in Example 1 has good specific capacity and cycle stability. In Comparative Example 1, no coating is performed, and the specific capacity and cycle performance of the battery assembled with the positive electrode material are significantly reduced compared with Example 1, indicating that the use of F-doped iron cobaltate can improve the electrochemical properties of the positive electrode material. In Comparative Examples 2 and 3, iron cobaltate nanoparticles and iron cobaltate nanosheets are used to coat the lithium-rich manganese-based positive electrode material, respectively. The specific capacity and cycle performance of the battery assembled with the corresponding prepared positive electrode materials are improved compared with Comparative Example 1, but decreased compared with Example 1.

[0088] from Figure 3 As can be seen from Table 1, the doping amount of F in Examples 1 to 3 is different, and the specific capacity and cycle performance of the battery composed of the corresponding positive electrode materials will fluctuate to a certain extent. In Example 6, no surfactant was added during the preparation of the positive electrode material, and the specific capacity and cycle performance of the battery composed of the corresponding positive electrode material were slightly reduced compared with Example 1. In Examples 7 and 8, the preparation process of the positive electrode material was adjusted, and the specific capacity and cycle performance of the battery composed of the corresponding positive electrode material fluctuated to a certain extent.

[0089] from Figure 4 As can be seen from Table 1, the addition amount of talc-like F ion-doped FeCo-LDH in Example 2, Example 4 and Example 5 is different, and the specific capacity and cycle stability of the battery composed of the corresponding prepared positive electrode materials will fluctuate to a certain extent.

[0090] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A positive electrode material for a lithium ion battery, characterized in that: The invention comprises a lithium-rich manganese-based positive electrode material and F-doped iron cobalt oxide coated on at least a portion of the surface of the lithium-rich manganese-based positive electrode material, wherein the chemical formula of the F-doped iron cobalt oxide is FeCo2O 4-0.5x F x , 0.01≤x≤0.06; the F-doped iron cobaltate is a nanosheet.

2. The lithium-ion battery positive electrode material according to claim 1, characterized in that The mass ratio of the F-doped iron cobaltate to the lithium-rich manganese-based positive electrode material is (0.03~0.1):

1.

3. The lithium ion battery positive electrode material according to claim 1 or 2, characterized in that: The chemical formula of the lithium-rich manganese-based positive electrode material is Li 1+m Mn 1-m-n X n O2, wherein: X is one or more of Ni, Co, Fe, Al, Zn, 0.1≤m≤0.5, 0≤n≤0.

4.

4. A method for preparing a positive electrode material for a lithium ion battery according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Dissolve iron salt and cobalt salt in water, then add an organic amine source for coprecipitation reaction to obtain FeCo-LDH; (2) adding the FeCo-LDH prepared in step (1) into a fluoride salt solution and reacting under closed conditions to obtain F-ion-doped FeCo-LDH; (3) ball-milling the lithium-rich manganese-based positive electrode material and the F-ion-doped FeCo-LDH prepared in step (2) to obtain a mixture; and sintering the mixture under an inert atmosphere to obtain a lithium-ion battery positive electrode material.

5. The method for preparing a positive electrode material for a lithium ion battery according to claim 4, characterized in that: In the step (1), after the iron salt and the cobalt salt are dissolved in water, the organic sulfonate or the organic sulfate is added before the organic amine source is added.

6. The method for preparing a positive electrode material for a lithium ion battery according to claim 4, characterized in that: In the step (1), the cobalt salt is one or more of cobalt acetate, cobalt sulfate and cobalt nitrate; The iron salt is one or more of ferrous acetate, ferrous sulfate and ferrous nitrate; The organic amine source is one or more of hexamethylenetetramine, azodicarbonamide, triethylenetetramine, and tetraethylenepentamine; The iron salt and the cobalt salt are added in a molar ratio of Fe to Co of 1:2; the molar ratio of the cobalt salt to the organic amine source is (0.03~0.1):(1.2~12).

7. The method for preparing a positive electrode material for a lithium ion battery according to claim 5, characterized in that: The organic sulfonate or organic sulfate is one or more of sodium dodecyl sulfate, sodium anthraquinone-2-sulfonate monohydrate, and sodium p-toluenesulfonate; the mass ratio of the cobalt salt to the organic sulfonate or organic sulfate is (0.03-0.1):(1-10).

8. The method for preparing a positive electrode material for a lithium ion battery according to claim 4, characterized in that: In the step (2), the fluoride salt is one or both of ammonium fluoride and sodium fluoride; the molar ratio of the F element in the fluoride salt to the Fe element in FeCo-LDH is (0.01-0.06):

1.

9. A solid-state battery, characterized in that: The positive electrode material is the positive electrode material for a lithium ion battery according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Preparation method of lithium manganate cathode material with ferri-containing compound coating

    CN105826550A

  • Potassium fluoroferrite modified Li-rich Mn-based layered cathode material for Li-ion battery and preparation method of cathode material

    CN107394200A